1998
DOI: 10.1159/000030196
|View full text |Cite
|
Sign up to set email alerts
|

Normal Ranges of Renal Physiological Parameters for Technetium-99m Mercaptoacetyltriglycine and the Influence of Age and Sex Using a Camera-Based Method

Abstract: 162 normal Chinese men and women underwent a 99mTc MAG3 renal study. Seventy-two males and 90 females were evaluated in 5 age groups: group 1, 61–80 years; group 2, 51–60 years; group 3, 41–50 years; group 4, 31–40 years, and group 5, 21–30 years. Each subject was required to fit the following criteria: (1) clinically no history of renal, urinary disorders and systemic diseases, normal blood pressure, kidney morphology, urinary examination and serum creatinine, and (2) for the gamma camera study nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…The mean postvoid/max whole kidney count ratio was <0.1 (Table 1) and the mean postvoid residual bladder volume was <30 mL ( Table 2). These results confirm and extend previous studies [46][47][48] and establish normal limits adjusted for age and gender. 45 The mean camera-based MAG3 clearance corrected for body surface area was 321 ± 69 mL/ min/1.73 m 2 (Table 3).…”
Section: Renogram and Voiding Parameters?supporting
confidence: 93%
“…The mean postvoid/max whole kidney count ratio was <0.1 (Table 1) and the mean postvoid residual bladder volume was <30 mL ( Table 2). These results confirm and extend previous studies [46][47][48] and establish normal limits adjusted for age and gender. 45 The mean camera-based MAG3 clearance corrected for body surface area was 321 ± 69 mL/ min/1.73 m 2 (Table 3).…”
Section: Renogram and Voiding Parameters?supporting
confidence: 93%
“…The renogram has been demonstrated to have a relatively wide variance in normal values due to anatomical variation in the location and depth of the kidneys, patient body habitus, inconsistencies between examiners in the selection of the region of interest and the time to peak, as well as a variety of algorithms for calculating renal clearance. The average variance between repeat scans by the same operator on consecutive days is +/- 2% but up to 8% variation has been reported in standardization trials [3, 4]. Other patient factors such as state of diuresis can compound this variation, further reducing the reproducibility of this method.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic comparative studies have shown, that the MAG 3 and OIH renogram curves are quite similar (Taylor et al ., 1986; Coveney & Robbins, 1987; Russell et al ., 1988; Bubeck et al ., 1990; Müller‐Suur et al ., 1990; Prenen et al ., 1991) and that MAG 3 has a higher plasma‐protein‐binding (Taylor et al ., 1986; Coveney & Robbins, 1987; Russell et al ., 1988; Bubeck et al ., 1990; Prenen et al ., 1991), a smaller volume of distribution (Bubeck et al ., 1990; Müller‐Suur et al ., 1990; Prenen et al ., 1991) and a lower affinity to the tubular system (Bubeck et al ., 1990; Russell et al ., 1988). Normal ranges of different physiological parameters for 99m Tc‐MAG 3 renography have been presented (Taylor et al ., 1986; Taylor et al ., 1988; Klingensmith et al ., 1994; El‐Galley et al ., 1998; Lin et al ., 1998) (Table 5). This study is the first European study.…”
Section: Introductionmentioning
confidence: 99%